THE IMPACT OF ORGANISATIONAL ORIENTATION RHETORIC ON FUNDRAISING SUCCESS IN SUSTAINABLE DEVELOPMENT - Andi Sumarlin K; Nurfatimah (Adisam Publisher, 2024)
This study aims to explore the impact of organizational orientation rhetoric on fundraising success in the context of sustainable development. The research method used is literature. The results show that clear and insightful rhetoric can achieve organizational goals towards sustainable development and fundraising success. Organizations that successfully communicate their sustainable values and goals in an authentic and transparent way are more likely to attract support from committed donors. An effective communication strategy proves essential in building trust and creating awareness among stakeholders, both of which are key factors in securing financial and non-financial support. In addition, the implementation of technological innovations and utilization of social media as part of sustainability-oriented fundraising strategies adds to the effectiveness of such efforts, contributing to more significant and sustainable outcomes.